Barriers to the implementation of clinical guidelines for maternal alcohol consumption in antenatal services: A survey using the theoretical domains framework. (29th May 2019) - Doherty, Emma; Kingsland, Melanie; Wiggers, John; Anderson, Amy E.; Elliott, Elizabeth J.; Symonds, Ian; Tully, Belinda; Dray, Julia; Wolfenden, Luke
Abstract: Issue addressed: The aim of this study was to assess potential barriers to the implementation of clinical guideline recommendations regarding maternal alcohol consumption by antenatal clinicians and managers. Methods: Cross‐sectional surveys of antenatal clinicians and managers employed in a New South Wales Local Health District were undertaken. Survey items were developed based on 11 domains of the Theoretical Domains Framework. Consistent with previous studies, a cut point of less than 4 was applied to mean values of survey items (range: 1‐5) to identify domains representing barriers to the implementation. Results: Thirty‐three antenatal clinicians and eight managers completed the surveys. For clinicians, the domains with the lowest mean values included "environmental context and resources" (ie, complexity of appointments and availability of supporting systems) (mean: 3.13, SD: 0.93); "social influences" (ie, expectations of others that alcohol will be addressed) (mean: 3.33, SD: 0.68); "beliefs about capabilities" (ie, confidence in providing guideline recommendations) (mean: 3.51, SD: 0.67); and "behavioural regulation" (ie, planning and responding to feedback) (mean: 3.53, SD: 0.64). For managers, "emotion regulation" (ie, stress in managing change) (mean: 2.13, SD: 0.64) and "environmental context and resources" (ie, complexities of managing change) (mean: 3.13, SD: 0.83) were the lowest scoring domains. Conclusions: The antenatal service environment and availability of resources appear to be primary barriers to both clinicians and managers implementing guidelines for maternal alcohol consumption. So what?: In the development of interventions to support the delivery of clinical guideline recommendations addressing alcohol consumption during pregnancy, a broad range of potential barriers at both the clinician and manager levels need to be considered and targeted by effective implementation strategies.